Influence of deep brain stimulation and levodopa on sensory signs in Parkinson's disease - Gierthmühlen, Janne; Arning, Philipp; Binder, Andreas; Herzog, Jan; Deuschl, Günther; Wasner, Gunnar; Baron, Ralf (Movement disorders, 2010)
To examine the effects of levodopa (L‐dopa) and deep brain stimulation of the subthalamic nucleus (STN‐DBS) on sensory symptoms and signs in Parkinson's disease (PD). Seventeen patients with PD were included. (1) Presence of sensory symptoms and (2) effects of L‐dopa and STN‐DBS on sensory symptoms and signs [assessed by quantitative sensory testing (QST)] were examined 6 months after starting STN‐DBS. In addition, in 12 of these patients, presence of sensory symptoms prior and post STN‐DBS was compared. Pain was most frequently nociceptive. In about 30–40%, pain and sensory symptoms were associated with PD motor symptoms. In most of these cases, pain responded to L‐dopa. Intensity of pain was reduced post STN‐DBS compared to pre STN‐DBS. L‐Dopa had no influence on detection thresholds, whereas STN‐DBS improved thermal detection thresholds. However, thermal and mechanical pain thresholds were uninfluenced by L‐dopa or STN‐DBS. Although some patients reported an improvement of pain with STN‐DBS or L‐dopa, objectively pain sensitivity as assessed by QST was not altered by STN‐DBS or L‐dopa suggesting that there is no evidence for a direct modulation of central pain processing by L‐dopa or STN‐DBS. © 2010 Movement Disorder Society